1990
DOI: 10.2307/1130952
|View full text |Cite
|
Sign up to set email alerts
|

Visiting the Wizard: Children's Memory for a Recurring Event

Abstract: The development of children's scripts for a recurring event was examined. 24 girls--2.5, 4, and 5.5 years of age--repeatedly experienced an initially novel episode (a trip to the "wizard's room") in a laboratory setting. Based on parents' ratings, the episode was defined as consisting of 26 actions organized into 7 activities. The sequential, spatial, and causal relations among the activities remained constant across episodes. Each child's knowledge of the recurring event was assessed by 4 probe conditions: fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Perhaps more importantly, the proportion of information in children's reports that was elicited by risky, closed-ended questions (i.e., questions more likely to result in short and inaccurate responses; Goodman & Aman, 1990, O'Callaghan & D'Arcy. 1989Peterson & Biggs, 1997;Price & Goodman, 1990;Saywitz, Goodman, Nicholas, & Moan, 1991) decreased significantly. These findings demonstrate that when forensic investigators use recommended interview procedures, they enhance the quality and quantity of the information elicited from alleged child victims.…”
Section: Discussionmentioning
confidence: 91%
“…Perhaps more importantly, the proportion of information in children's reports that was elicited by risky, closed-ended questions (i.e., questions more likely to result in short and inaccurate responses; Goodman & Aman, 1990, O'Callaghan & D'Arcy. 1989Peterson & Biggs, 1997;Price & Goodman, 1990;Saywitz, Goodman, Nicholas, & Moan, 1991) decreased significantly. These findings demonstrate that when forensic investigators use recommended interview procedures, they enhance the quality and quantity of the information elicited from alleged child victims.…”
Section: Discussionmentioning
confidence: 91%
“…Although the activities were linked in the sense that they all were activities that occurred when "Scott" came to play with the children, the individual activities were not logically or causally connected. Several scholars have found that children are faster to script an event that is causally connected rather than merely temporally related (Bauer & Fivush, 1992;Bauer & Shore, 1987;Price & Goodman, 1990;Ratner, Smith, & Dion, 1986). A more causally connected event may have facilitated the process of scripting for the younger children and heightened their suggestibility to a level equal to or greater than the level of suggestibility of the older children.…”
Section: Discussionmentioning
confidence: 99%
“…Young children often have difficulty in retrieving detailed memories in response to purely verbal free recall questions, perhaps especially in formal interviews held in decontextualized settings (e.g., Donaldson, 1978;Keary & Fitzpatrick, 1994;Price & Goodman, 1990). Purely verbal interviews might not provide the ''stimulus support" needed for preschoolers to access their recollections fully.…”
Section: Interviewing Strategiesmentioning
confidence: 99%
“…As a result, open-ended questioning may lead to underestimation of the scope of young children's memories. To prompt preschoolers' retrieval, stimulus support as afforded by memory cues such as props can be advantageous (Price & Goodman, 1990).…”
Section: Interviewing Strategiesmentioning
confidence: 99%